DOCTRINAL VIEWS ON THE MECHANISMS OF PREVENTION OF CRIMES COMMITTED BY WOMEN (World Bulletin of Management and Law, 2022)
In this article, the author conducted a systematic analysis of existing doctrinal views on crimes committed by women and their prevention, their development trends, uniqueness and facts in this regard. Having studied the issues of applying the doctrinal approaches stated by the author to the mechanisms of prevention of crimes committed by women in the conditions of Uzbekistan, proposals have been developed in this regard
Keywords: Violence; female crimes; infanticide; murder